Penerapan Keselamatan dan Kesehatan Kerja (K3) pada Atraksi Adventure Tourism di Kawasan Air Terjun Aling-Aling Sambangan - Wiratami, Rut; Bhaskara, Gde Indra (JURNAL DESTINASI PARIWISATA; Vol 5 No 2 (2017): VOL 5, NO 2 (2017): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATA, 2018)
Tourist  safety is an important aspect in tourism activities and must have serious attention from the  manager of a tourism destination. It is also one of  tourist  satisfaction over the service which  further will imposes image of the  destination around the world.  Sambangan tourism village is  one of the tourist destinations in North Bali which is currently popular to domestic and  foreign tourists.  There are two unique attractions become flagship attractions that are sliding and jumping.  Along with the development of an increasing tourist visits since last few years, problems began appear. An  accident even cause  the  loss of life and one of them is a local guide who made a living in that area. Therefore, this research is considered  necessary and important in order to find out how the  application of safety and health of  work have been done so far. Data obtained through library studies, participatory observation and interviews with the determined informants . This research found that the safety and health aspects of work in Sambangan tourism village are still simple due to the limitations of funding and a lack of understanding in the health aspects so that the implementation of health and safety of work is done based on understanding. Therefore, in the future a further research is needed related to the health aspects of a medical, increasing of security aspects in the location of tourists attraction and also the attention and support from the government especially tourism department.   Keywords : Safety and Healthy, Adventure Tourism, Attraction, Waterfall.